PERANAN WANITA TANI DALAM PENINGKATAN EKONOMI PADA KEGIATAN PENGEMBANGAN USAHA MINA PEDESAAN PERIKANAN BUDIDAYA (PUMP-PB) DI KABUPATEN BULUKUMBA - Rosliawati Arfah; Ilmiah Ilmiah; Harlina Harlina (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
This research aims to determine the role female farmers in development of rural aquaculture and the factors that influence the role of women farmers in rural aquaculture Development. This research was conducted in January to February 2020 in Bulukumba Regency. The t test analysis method was the comparative test. The results indicate that the Role of Women Farmers in the Development of Rural Aquaculture in Bulukumba Regency had a positive impact and the average income of the groups receiving assistance had increased incomes. The results of the calculation of multiple regression analysis show that the factors that influence the role of women farmers in the economic improvement was age, degree level, land area, and level of experience, while the nature of work and the number of dependents do not directly affect the increase in income of farmers in economic improvement activities.